WebQuest as a Media in Teaching Vocabulary for Young Learners - Kuncahyo, Nanda Lintang Utari; Masykuriyah, Hikmatul; Jannah, Ida Miftakhul (ICONELT, 2022)
One example of a web-based learning media format that enables teachers to assign a task to students so that they can explore and analyze information is WebQuest. By gathering and analyzing data from the internet, WebQuest can assist students in providing fresh perspectives on issues. Higher-order thinking abilities like problem-solving and critical analysis might result from a new understanding of something. Additionally, young learners can learn vocabulary with WebQuest. Moreover, WebQuest is also a means to teach vocabulary material to young learners. The researcher tries to find out effective media to teach English to young learners. After conducting research on the WebQuest media for young learners using qualitative research design, the research appears with significant results. The data was collected in SDN 1 Gedongan Mojokerto by involving the English teachers as subjects of this research. The English teacher comes from the Lecturer of Islamic State University of Sunan Ampel Surabaya and the elementary school teacher to find out whether this media is effective or conversely ineffective. As the researchers have established the research that used the R&D method or which is well known as Research and Development method, the result is beyond the expectation of using WebQuest for English teaching media. For instance, the teacher confirms that this kind of digital media is eligible in becoming a medium for young learners. This statement is based on what WebQuest media is for. In the material design, this WebQuest is very flexible in maintaining the contents shown, like it will be able to be embedded in the other kinds of online platforms of media to fulfill the content materials needed. The teacher has also given the statement of admiration whereas the media of WebQuest is presumed as a creative breakthrough in this digital era principally for young learners. WebQuest is one of the web-based electronic media that can be implemented in teaching vocabulary to young learners. By researching and analyzing the information, WebQuest aims to assist students in developing their critical thinking and problem-solving skills. All in all, the implementation of WebQuest can be said to be effective to be used for teaching and learning processes for 3rd-grade elementary school.